Exploring the Impact of Good Corporate Governance on Firm Value with CSR Disclosure as a Moderating Variable in IDX - Winarsih; Fannisa Faradilla Sari; Azizah Azmi Khatamy (Proceeding International Conference on Accounting and Finance, 2025)
This study identifies the influence of Good Corporate Governance dimensions (Independent Board of Commissioners, Board of Commissioners, Board of Directors, Institutional Ownership, Managerial Ownership, and Audit Committee) on Firm Value with Corporate Social Responsibility (CSR) as a moderating variable. The population in this study were companies included in the Kompas 100 index for the 2019-2022 period. The sample was selected using a purposive sampling technique and a final sample of 44 was obtained. The data used were secondary or quantitative data with an explanatory design and multiple linear regression analysis to test the hypothesis. The analysis technique used in this study was Eviews. The results showed that the Board of Commissioners and Independent Board of Commissioners did not have a significant effect on firm value. The Board of Directors, Institutional Ownership, Managerial Ownership, and Audit Committee have a significant effect on Firm Value. CSR cannot moderate the relationship between the board of commissioners and institutional ownership on firm value, CSR can moderate the relationship between the Independent Board of Commissioners, Board of Directors, Managerial Ownership, and Audit Committee on firm value.